SAFE PLAY UNTUK MEMBANGUN KESIAPSIAGAAN ANAK USIA DINI TERHADAP BENCANA DI DAERAH ISTIMEWA YOGYAKARTA - Melia Widayanti; Mallevi Agustin Ningrum; Kartika Rinakit Adhe; Muhammad Naufal Fairuzillah (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to improve early childhood education (ECE) teachers’ knowledge and skills in understanding disaster mitigation through a safe play approach. The program was conducted at IGTKI Depok District, Special Region of Yogyakarta, involving 28 ECE teachers using a one-group pre-test–post-test design. The training was implemented through three main methods: lectures, assignments, and group projects. Lectures were used to provide participants with knowledge related to disaster mitigation concepts, while assignments and projects facilitated participants in designing educational games based on disaster preparedness. The results showed an increase in participants’ average scores from 57.50 in the pre-test to 80.00 in the post-test, with an improvement percentage of 39.13%. In addition, participants successfully developed several disaster mitigation-based educational game designs, including preparedness-themed snakes and ladders, evacuation puzzles, and disaster mitigation songs. These findings indicate the potential effectiveness of the safe play approach in supporting teachers to integrate disaster preparedness concepts into early childhood learning activities and contribute to creating more disaster-resilient school environments.